FISH POSITION DETERMINATION WITH GLOBAL POSITIONING SYSTEM (GPS) - Henwandar Henwandar; Luyung Dinaini, SKom, MMSI (Jurnal Sistem Komputer, 2004)
One of the few tools of the new information today is the Global Positioning System(GPS) used to determine precise location information of the existence of objects onearth. GPS uses satellites that can serve to identify the location, direction andmovement.Therefore, the authors raised the theme of use of GPS technology to record thelocations of fish were found by fishermen in its operations. Since the GPS canprovide position quickly and precisely at all times and in all weather conditions, thenwith a GPS receiver and map navigation, the fishing like fishermen will be able tosafely explore the ocean. Thus expected to catch can be increased and can increasefuel, travel and time.